Presence phenomena in parkinsonian disorders: Phenomenology and neuropsychological correlates. (30th April 2020) - Reckner, Erin; Cipolotti, Lisa; Foley, Jennifer A.
Abstract : Introduction: The feeling of a presence that occurs in the absence of objectively identifiable stimuli is common in parkinsonian disorders. Although previously considered benign and insignificant, recent evidence suggests that presence phenomena may act as the gateway to more severe hallucinations and dementia. Despite this, we still know relatively little about these phenomena. Objective: To examine parkinsonian disorder patients' subjective experience of presence phenomena, and retrospectively analyse their cognitive correlates, in order to elucidate the emergence of information processing deficits in parkinsonian disorders. Methods/Design: 25 patients who endorsed presence phenomena were asked to complete a semi‐structured interview about their experiences. The cognitive profiles of these patients were then compared to those of age‐ and education‐matched patients who denied presence phenomena. Results: Patients described the presence as mostly that of an unknown human with neutral valence. Patients who described it as unpleasant were noted to also demonstrate elevated anxiety. Patients who identified the presence as a known person, described it as touching them, or interacted with the presence emotionally or physically demonstrated reduced insight. Patients with presence phenomena demonstrated more frequent impairments in visual processing, executive function and speed of processing. Conclusions: Presence phenomena occur in the company of advancing cognitive impairment and involvement of the posterior cortical functions. Initially encountered as a neutral spatial skeleton, the experience is then shaped by the patient's affective state and level of insight.